Change of Lip Curvature Through Extraction and Non-Extraction Orthodontic Treatment - Boosung Kim; Young Ho Kim; Soo Min Lee; Un-Bong Baik; Janghoon Ahn; Jeong Won Shin; Hwa Sung Chae (Applied Sciences)
Backgroud: Orthodontic treatment plans face challenges when deciding on tooth extraction, particularly when the retraction of incisors leads to a flattening of the lip curvature. Despite the significance of this issue, quantitative measurements of curvature have not been previously undertaken. This study presents novel soft tissue measurements, namely SAL (A’toSn-Ls) depth, SAL angle, PBL (B’toLi-Pg) depth, and angle, as tools for assessing lip curvature. The aim of this study was to assess whether new parameters demonstrated more pronounced flattening of the upper and lower lips in the extraction group compared to the non-extraction group. Methods: A total of sixty-two patients diagnosed with skeletal Class I malocclusion and treated with extraction or non-extraction orthodontic treatment were included and compared. Cephalometric measurements were analyzed and compared between the initial and final stages of treatment. Results: The difference in SAL (1.99°) and PBL (4.41°) angles and other soft tissue measurements between the groups was not statistically significant. Multiple regression analysis yielded the equation: ΔSAL = 0.66ΔU1 tip – 0.98ΔL1 tip – 1.58. Conclusions: Flattening of the upper lip was not significantly displayed on moderate anchorage. Consequently, orthodontic treatment accompanying the retraction of the upper incisors does not always result in obtuse lip profiles.